Metode Ummi Meningkatkan Kemampuan Membaca Al-Qur'an di Universitas Nahdlatul Ulama Al Ghazali (UNUGHA) Cilacap - Nisaul Mukaromah; Muh Hanif (Tarbiatuna: Journal of Islamic Education Studies, 2024)
This research aims to analyze the application of the Ummi method in improving the ability to read the Al-Qur'an at UNUGHA Cilacap. The aim is to provide a better understanding of the factors that influence the effectiveness of Al-Qur'an learning in the academic environment, as well as applying the ummi method to improve students' Al-Qur'an reading skills, with a focus on case studies at UNUGHA Cilacap. Through a case study approach, presenting an effective method for improving skills in reciting the Koran through the Ummi method. Reading the Koran proficiently is an important skill for Muslim students. However, many people face difficulties in mastering the correct recitation techniques. This research explores the effectiveness of the Ummi Method—an innovative teaching approach—in developing strong Al-Quran reading skills among students at Al Ghazali State Islamic University, Cilacap. Through the use of a qualitative case study design, we observed Ummi Method classes, interviewed enthusiastic students and dedicated tutors, and examined evaluation results. These findings reveal how the Ummi Method engages students with a fun yet rigorous step-by-step process. By utilizing repetition, an emphasis on clear pronunciation, and a caring learning environment, students gain confidence and improve their skills significantly. Real-life motivational examples from tutors also inspire spiritual and character development. Students appreciate learning at their own pace through this simple yet comprehensive system. The evaluation scores support that the Ummi Method improves the quality of reading, knowledge of Tajwid rules, and love of the Al-Quran. This research provides valuable insights into effective teaching approaches that address the needs of modern Muslim learners. The successful application of the Ummi Method at Al Ghazali State Islamic University Cilacap shows its potential in optimizing academic achievement and also strengthening faith in other educational contexts. This method is based on the rules of tajwid, makharijul letters, gharib, and tartil rules. Recommendations include curriculum improvements and facility support to improve students' ability to read the Koran. Further studies are needed for a deeper understanding. The findings of this research provide valuable insight for the development of effective learning strategies and solutions to overcome the challenges faced by students in studying the Koran.